2020
DOI: 10.1002/dc.24478
|View full text |Cite
|
Sign up to set email alerts
|

Salivary gland fine‐needle aspiration cytology with the application of the Milan system for risk stratification and histological correlation: A retrospective 6‐year study

Abstract: Background: The Milan System for Reporting Salivary Gland Cytopathology (MSRSGC) is based on risk stratification. We presented our experience with fineneedle aspiration cytology (FNAC) for the diagnosis of salivary glands lesions by applying the MSRSGC categorization to the cytological diagnoses, and determined risk of malignancy (ROM) for each category. Methods: Fine-needle aspiration cytology of salivary gland lesions performed over a 6-year period was retrieved. FNAC results were retrospectively categorized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…The use of cytology confirmed its relevant role as for a 94.4% diagnostic accuracy in discriminating benign from malignant neoplasms. Moreover, their result confirmed that the ROM for each category was perfectly in line with the MSRSGC ROM in each diagnostic category [49].…”
Section: The Third Year Of Publications Using the Milan System-2020supporting
confidence: 57%
See 2 more Smart Citations
“…The use of cytology confirmed its relevant role as for a 94.4% diagnostic accuracy in discriminating benign from malignant neoplasms. Moreover, their result confirmed that the ROM for each category was perfectly in line with the MSRSGC ROM in each diagnostic category [49].…”
Section: The Third Year Of Publications Using the Milan System-2020supporting
confidence: 57%
“…The data from 2018 and 2019 were confirmed in 2020 with the publication of different papers confirming the useful role of the MSRSGC system [20][21][22][23][24][25]27,[46][47][48][49][50].…”
Section: The Third Year Of Publications Using the Milan System-2020mentioning
confidence: 80%
See 1 more Smart Citation
“…These categories have been validated by multiple retrospective reviews of cytopathology reports across the globe since the introduction of the MSRSGC in 2015. [6][7][8] Viswanathan et al in 2018 performed a retrospective analysis of 627 salivary gland FNAs applying the MSRSGC and found strong correlation between the proposed risk of malignancy and the actual rate of malignancy after sialoadenectomy. 9 Rivera Rolon et al reviewed 208 salivary gland FNAs in 2020 that confirmed these findings and suggested a diagnostic accuracy of 94.4% when distinguishing benign versus malignant pathology.…”
Section: Discussionmentioning
confidence: 99%
“…The observed rate of malignancy in our dataset is similar to the proposed risk of malignancy by the MSRSGC. These categories have been validated by multiple retrospective reviews of cytopathology reports across the globe since the introduction of the MSRSGC in 2015 6–8 . Viswanathan et al in 2018 performed a retrospective analysis of 627 salivary gland FNAs applying the MSRSGC and found strong correlation between the proposed risk of malignancy and the actual rate of malignancy after sialoadenectomy 9 .…”
Section: Discussionmentioning
confidence: 99%